Demographic, Clinical, and Treatment Factors That Affect the Five Years Survival of Thyroid Cancer Patients - Alika Ristama Nigandiva; Daan Khambr; Saptino Miro; Novita Ariani; Rony Rustam; Dina Arfiani Rusjdi (Publikasi Inspirasi Indonesia, 2024)
Thyroid cancer is the most common malignancy of the endocrine glands, the incidence of thyroid cancer in Indonesia ranks ninth after other types of cancer, it is known that the survival rate of thyroid cancer is better when compared to other types of cancer because thyroid cancer has a slow growth rate. Several demographic factors such as age and gender, clinical factors and treatments factors can affect the survival rate of thyroid cancer patients. This study was conducted to analyze the influence of demographic, clinical, and management factors on thyroid cancer survival rates at Dr. M. Djamil Padang Hospital. This study is an observational analytic study with a retrospective cross-sectional design. Sampling was done by total sampling technique. Data collection is done through patient medical record data. The results showed a five-year survival rate for thyroid cancer of 86.7%. Age, histopathological type, metastases, tumor extension, and management were significantly related to survival (p=0.013) (p=0.000), (p=0.001), (p=0.000) and (p=0.001). Factors that have a significant relationship with survival rate are age, histopathological type, tumor extension, treatment, and metastases, and those that most influence survival rate are non-operative management and regional extension